PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN KOMIK EDUKASI TERHADAP LITERASI BACA DAN TULIS PESERTA DIDIK KELAS II SD NEGERI KLECO 1 SURAKARTA TAHUN AJARAN 2024/2025 - Putri Agustin Nurjanah; Sri Suryanti, Hera Heru; Rizkasari, Elinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The objective of this study is to determine whether there is an effect of using educational comic media on the reading and writing literacy skills of second-grade students at SD Negeri Kleco 01 Surakarta. This study employs a quantitative approach with a Pre-Experimental method, using the One Group Pre-test Post-test design. The population of this research consists of all second-grade students of SD Negeri Kleco 01 Surakarta in the 2024/2025 academic year, totaling 112 students. The sample includes 28 students from class II A of the same school in the 2024/2025 academic year, selected using a Non-Probability Sampling technique. Data collection was conducted through tests, interviews, observations, and documentation. The data analysis techniques used were the normality test and hypothesis testing with the Paired Sample T-test. Based on the research results and data analysis at SD Negeri Kleco 01 Surakarta, it can be concluded that there is a significant difference in students’ reading and writing literacy skills when using educational comic media. This finding is supported by the results of the Paired Sample T-test, where the sig. (2-tailed) value of 0.000 < α (0.05), indicating a significant difference in learning outcomes before and after the treatment. The average pre-test score was 48.85, while the average post-test score increased to 88.42. These results demonstrate that students who learned using educational comics achieved better performance compared to before using the media. Therefore, this study shows that the use of educational comic media has a significant effect on improving reading and writing literacy skills.